Aesthetic implant: A new era of aesthetic dentistry (Bangabandhu Sheikh Mujib Medical University Journal, 2016)
The dental implant is used to replace the natural tooth system. It requires comprehensive preoperative planning and precise surgical execution. In this case report, a 45 year old male presented with missing upper left maxillary central incisor which was extracted 5 months back. He had discomfort during function and unwillingness to smile. He wanted to replace that edentulous area. The treatment options for replacing the missing tooth were discussed with the patient. Finally, with patient's consent the decision was made to replace that edentulous area with an implant supported porcelain fused to metal prosthesis in an esthetic manner. Recall visits exhibited patient's high-level confidence of smile with optimum satisfaction and successful aesthetic outcome.